Supporting Bioscience Innovation in Eastern Africa - Virgin, Ivar; Ecuru, Julius; Alemu, Abebe; Gasingirwa, Christine; Karembu, Margaret; Opati, Linda; Nyange, Nicholas; Omari, Jane; Teklehaimanot, Haileselassie (Stockholm Environment Institute, 2016)
Bioscience innovations have significant potential to contribute to sustainable development and economic growth in Eastern Africa. The study is focused on bioscience innovation in Ethiopia, Kenya, Rwanda, Tanzania and Uganda. We examine a selection of bioscience technology clusters and the emerging innovation systems that correspond to each, from the perspective of technological innovation systems. We then identify barriers and enabling conditions for moving bioinnovations from the laboratory to the market in Eastern Africa.
Keywords: bioscience; innovation; laboratory